Structure–Activity Relationship Study of the Cleistriosides and Cleistetrosides for Antibacterial/Anticancer Activity - Shi, Pei (American Chemical Society, 2012)
[Image: see text] Two known cleistriosides and six known cleistetrosides were synthesized and evaluated for anticancer and antibacterial activities. This study, for the first time, reports anticancer activity and comprehensively the antibacterial activity for these oligosaccharide natural products. In addition, two new unnatural cleistetroside analogues were synthesized and tested. Biological activities for the 10 oligosaccharides against B. subtilis were found to range between 4 and >64 μM and for NCI-H460 human lung cancer epithelial cells between 7.5 and 90.9 μM. Similar activities were found for seven of the oligosaccharides against the NCI panel of 60 cell lines. The degree of acylation and location of the specific acetate groups had significant effects on the anticancer and antibacterial activity of both the cleistriosides and the cleistetrosides.